Emotion Regulation Tendencies and Leadership Performance: An Examination of Cognitive and Behavioral Regulation Strategies - Torrence, Brett S.; Connelly, Shane (Frontiers in Psychology, 2019)
Emotion regulation is advocated to be an important competence underlying effective leadership given the task demands and interpersonal stressors facing organizational leaders. Despite the recognition of emotion regulation processes in leadership literature, there is a need for additional theorizing and empirical research on the specific cognitive and behavioral strategies utilized by leaders. This effort attempts to address this gap by examining individual tendencies in four emotion regulation strategies, situation modification, attentional deployment, cognitive reappraisal, and suppression, and their association with leadership task performance. Results provide partial support suggesting that situation modification and cognitive reappraisal are positively related to leadership performance. Suppression was found to relate negatively with performance. Emotion regulation strategies were also found to account for variance in leadership performance above and beyond other emotion-related individual differences. Taken together, these findings suggest that certain regulation processes may be more functional for leaders and extend emotion regulation research into the leadership domain. Theoretical and practical implications of this study are discussed.